2018
DOI: 10.1017/pen.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Human Metacognition Across Domains: Insights from Individual Differences and Neuroimaging

Abstract: Metacognition is the capacity to evaluate and control one’s own cognitive processes. Metacognition operates over a range of cognitive domains, such as perception and memory, but the neurocognitive architecture supporting this ability remains controversial. Is metacognition enabled by a common, domain-general resource that is recruited to evaluate performance on a variety of tasks? Or is metacognition reliant on domain-specific modules? This article reviews recent literature on the domain-generality of human me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
187
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(237 citation statements)
references
References 119 publications
(189 reference statements)
27
187
1
Order By: Relevance
“…This suggests the role of left IFG operating similarly around 300 ms whether a decision is committed or observed. Of note, the quest for domain-general mechanisms of confidence (Faivre et al, 2018, Rouault et al, 2018) is hindered by the fact that our paradigm alternated short blocks of active and observation conditions, which could potentially inflate correlations in confidence due to confidence leaks across trials (Rahnev et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the role of left IFG operating similarly around 300 ms whether a decision is committed or observed. Of note, the quest for domain-general mechanisms of confidence (Faivre et al, 2018, Rouault et al, 2018) is hindered by the fact that our paradigm alternated short blocks of active and observation conditions, which could potentially inflate correlations in confidence due to confidence leaks across trials (Rahnev et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous works help us predict candidate brain regions in which we should see the correlates of confidence at the private decision-making stage. A variety of areas within prefrontal, parietal and occipital cortices have been linked to confidence 10 including dorsolateral prefrontal cortex 11,12 , perigenual anterior cingulate cortex 13 and ventromedial prefrontal cortex for valuebased 14,15 and perceptual decisions 16 . Importantly, all of these studies exclusively focused on isolated individuals making private decisions [17][18][19] thus offering a clear set of target areas for neural activations in the private stage of our framework (Figure 1, left panel).…”
Section: Introductionmentioning
confidence: 99%
“…They found that accurate metacognitive evaluation on a perception task positively correlated with the diffusion anisotropy underlying the ACC, whereas accurate metacognitive evaluation on a memory task positively correlated with the diffusion anisotropy of the white matter underlying the IPL, indicating metacognition in different cognitive domains might rely on distinct neural resources. Nevertheless, Baird and colleagues did not control for the local task properties nor the metrics quantifying the perceptual and mnemonic metacognitive ability, which might bias the comparison across domains (Rouault et al, 2018b).…”
mentioning
confidence: 99%